Prevalence of Gastrointestinal Protozoa Infection in Piglets on Pig Breeding Farms in Gianyar Regency, Bali. - Eukaristia Junitha; I Wayan Sudira; Nyoman Adi Suratma; I Putu Cahyadi Putra (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Gastrointestinal protozoan infections, including those caused by Eimeria sp., Cystoisospora sp., Entamoeba sp., and Balantidium sp., can result in significant livestock losses. This study aimed to ascertain the prevalence of gastrointestinal protozoan infections and compare the prevalence rates between suckling and weaned piglets on pig breeding farms in Gianyar Regency. A total of 216 piglet fecal samples were analyzed, comprising 87 samples from the suckling phase and 129 from the weaned phase. Gastrointestinal protozoa were identified through morphological examination, utilizing the sedimentation method for Balantidium sp. and Entamoeba sp., and the saturated salt flotation method for Coccidia examination. Differences in the prevalence of protozoan infections between suckling and weaned piglets were assessed using the Chi-Square Test with IBM SPSS Statistics. The findings indicated that the prevalence of gastrointestinal protozoan infections in piglets on breeding farms in the Gianyar Regency was 51.85% (112/216). The identified protozoa included Balantidium sp. (37.96%), Entamoeba sp. (25.92%), and Coccidia (7.87%). The prevalence of gastrointestinal protozoan infections in suckling piglets was 35.63% (31/87), whereas that in weaned piglets was 62.79% (81/129), demonstrating a significant difference (p=0,0001). There were diverse infections, with some piglets harboring more than one protozoan type. The prevalence rate of gastrointestinal protozoan infections was deemed high, with weaned piglets exhibiting greater susceptibility to infection than suckling piglets.